EFFECTS OF SOIL WATER AVAILABILITY AND ORGANIC MATTER CONTENT ON FRUIT YIELD AND SEED OIL CONTENT OF CASTOR BEAN1 - Lacerda,Rogério D. de (2020)
ABSTRACT The objective of this study was to assess the sensitivity of the castor bean cultivar “BRS 188 Paraguaçu” to available soil water for plants and soil organic matter content based on their effects on fruit yield and seed oil content. A 2 × 4 factorial experiment was conducted from October 2008 to March 2009 under field conditions using randomized complete block design; two soil organic matter contents (5.0 and 25.0 g·kg−1) and four available soil water levels for plants at the irrigation time (70, 80, 90, and 100% of the total available soil water) with three replicates were tested. On each experimental unit measuring 100 m2, 50 plants were cultivated with a spacing of 2 m × 1 m (24 useful and 26 border plants). Analysis of variance (F test) was performed; qualitative factors (soil organic matter) were compared by Tukey's test and quantitative factors (available soil water) by regression analysis. Increased soil organic matter and available soil water for plants substantially increased productivity; however, seed oil content, mean 100-seed mass, mean 100-fruit mass, and seed:fruit ratio were affected by available soil water content alone. Therefore, the tested cultivar is sensitive to reduced available soil water content, which severely decreases its productivity.